Basis of preparation of effective fertilizers and agrochemicals method of discrete-pulse input energy - Draganov, B.; Borhalenko, Y. (Energy and Automation, 2015)
The mathematical model of heat and mass transfer and hydrodynamic processes specified discrete input pulse energy. The analysis of data obtained by the SFD model. The specified level of efficiency of fertilizers and agrochemicals during their homogenization discrete input pulse energy.